Effects of Yb and Sc co-doping on the thermal properties and CMAS corrosion of garnet-type (Y3-xYbx)(Al5-xScx)O12 ceramics. Issue 5 (1st March 2023) - Li, Yingxin; Qian, Wei; Hua, Yinqun; Ye, Yunxia; Dai, Fengze; Cai, Jie
Abstract: Thermal barrier coatings with excellent thermal performance and corrosion resistance are essential for improving the performance of aero-engines. In this paper, (Y3-x Ybx )(Al5-x Scx )O12 (x = 0, 0.1, 0.2, 0.3) thermal barrier coating materials were synthesized by a combination of sol-gel method and ball milling refinement method. The thermal properties of the (Y3-x Ybx )(Al5-x Scx )O12 ceramics were significantly improved by increasing Yb and Sc doping content. Among designed ceramics, (Y2.8 Yb0.2 )(Al4.8 Sc0.2 )O12 (YS-YAG) showed the lowest thermal conductivity (1.58 Wm −1 K −1, at 800 °C) and the highest thermal expansion coefficient (10.7 × 10 −6  K −1, at 1000 °C). In addition, calcium-magnesium- aluminum -silicate (CMAS) corrosion resistance of YS-YAG was further investigated. It was observed that YS-YAG ceramic effectively prevented CMAS corrosion due to its chemical inertness to CMAS as well as its unique and complex structure. Due to the excellent thermal properties and CMAS corrosion resistance, YS-YAG is considered to be prospective material for thermal barrier coatings.